A Case Series: Adjunctive Treatment of Major Depressive Disorder in the Geriatric Population with the Methylphenidate Patch - Patel, Kamal; Collins, Ashley; Holroyd, Suzanne; Benja Lamyaithong, Andre (Case Reports in Psychiatry, 2019)
Major depressive disorder can affect anyone regardless of age. In geriatric populations depression is often overlooked and untreated, which subsequently may lead to serious consequences. Almost one third of elderly patients with depression fail to respond to initial treatment and require adjunctive treatment. Methylphenidate is one such option, which is seldom used in the geriatric population to treat depression despite reports of improvement in symptoms of mood within a brief period of time. Methylphenidate is also available in a patch formulation that can be used in patient’s nonadherent to the medication, which is reported to be an issue in as many as 75% of the geriatric population. Here we present three geriatric patients who were diagnosed with recurrent severe major depressive disorder without psychotic features. The three patients responded well with methylphenidate as adjunctive treatment to conventional antidepressants.